Implementation and effectiveness of a linkage to HIV care intervention in rural South Africa (ANRS 12249 TasP trial). - Mélanie Plazy; Adama Diallo; Thabile Hlabisa; Nonhlanhla Okesola; Collins Iwuji; Kobus Herbst; Sylvie Boyer; France Lert; Nuala McGrath; Deenan Pillay; François Dabis; Joseph Larmarange; et al. (PLoS ONE, 2023)
Background Timely linkage to care and ART initiation is critical to decrease the risks of HIV-related morbidity, mortality and HIV transmission, but is often challenging. We report on the implementation and effectiveness of a linkage-to-care intervention in rural KwaZulu-Natal, South Africa. Methods In the ANRS 12249 TasP trial on Universal Testing and Treatment (UTT) implemented between 2012-2016, resident individuals ≥16 years were offered home-based HIV testing every six months. Those ascertained to be HIV-positive were referred to trial clinics. Starting May 2013, a linkage-to-care intervention was implemented in both trial arms, consisting of tracking through phone calls and/or home visits to "re-refer" people who had not linked to care to trial clinics within three months of the first home-based referral. Fidelity in implementing the planned intervention was described using Kaplan-Meier estimation to compute conditional probabilities of being tracked and of being re-referred by the linkage-to-care team. Effect of the intervention on time to linkage-to-care was analysed using a Cox regression model censored for death, migration, and end of data follow-up. Results Among the 2,837 individuals (73.7% female) included in the analysis, 904 (32%) were tracked at least once, and 573 of them (63.4%) were re-referred. Probabilities of being re-referred was 17% within six months of first referral and 31% within twelve months. Compared to individuals not re-referred by the intervention, linkage-to-care was significantly higher among those with at least one re-referral through phone call (adjusted hazard ratio [aHR] = 1.82; 95% confidence interval [95% CI] = 1.47-2.25), and among those with re-referral through both phone call and home visit (aHR = 3.94; 95% CI = 2.07-7.48). Conclusions Phone calls and home visits following HIV testing were challenging to implement, but appeared effective in improving linkage-to-care amongst those receiving the intervention. Such patient-centred strategies should be part of UTT programs to achieve the UNAIDS 95-95-95 targets.